Effectiveness of Foot Care in Preventing Skin Damage and Risk of Diabetic Foot Wounds in Diabetes Mellitus Patients - Jumain; Noviany Banne Rasiman (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Diabetes mellitus (DM) type II is a disease characterized by increased blood sugar levels which can cause many complications. The complications of DM that often occur are skin damage and diabetic foot wounds, because in general patients are not aware of the presence of ulcers due to the neuropathy they are experiencing. The risk of foot injuries can increase the need for treatment and care in patients. However, the risk of foot injuries can be detected early by the patient independently by carrying out regular examinations of the patient's feet. Providing foot care can reduce the incidence of skin damage and the risk of diabetic foot wounds. Objective: The aim of the research is to analyze the effectiveness of foot care in preventing skin damage and the risk of diabetic foot wounds in diabetes mellitus patients. Method: This research method uses a quasi-experimental design with a pretest posttest one group design. This research was conducted at the Undata Hospital in the Bougenvile room with a population of 31 participants. The selection of respondents was based on inclusion criteria, namely: age ? 30 years and suffering from DM. Result: The results of the analysis used the paired sample t-Test. The average skin damage prevention score for DM patients before giving foot care was 2.97 and the skin damage prevention score after being given foot care was 2.52, respectively, experiencing a decrease in skin improvement of 0.45. These results show that the average value of diabetic ulcer risk for DM patients before being given foot care was 2.81 and the average value after being given foot care was 2.16 with a difference in improvement in the risk of diabetic ulcers of 0.65 which shows that the p-value is 0.000 < ? (0.005) then H0 is rejected and H1 is accepted. This shows that there is an effect after being given effective foot care on preventing skin damage and the risk of diabetic ulcers in DM patients at Undata Regional Hospital. Conclusion: This research proves the influence of the effectiveness of foot care on preventing skin damage and the risk of diabetic ulcers in DM patients at Undata Hospital.